Modelling of time related drying changes on matte coated paper with artificial neural networks - ŞAHİNBAŞKAN, TÜRKÜN (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this study, the determinability of time related colour changes in prints made using ink that dries on matte coated paper with the offset printing technique and infrared method, has been investigated with artificial neural networks after analysis of the experimental and numerical methods. In the experimental part a ECI 2002 CMYK test scale is printed on a 135 g/m(2) matte coated. The prints obtained were measured with a spectrophotometer at certain intervals and by converting the reflection data obtained into the CIELAB colour description spectrum, time related changes in printed colours have been determined. In the empirical study however, colour changes in prints made on matte coated paper using inks that dry with the infrared method are modelled numerically. The average deviation has been found to be 0.4%. As a result, artificial neural networks can be used with the aim to digitally calculate time related colour changes in the offset printing system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Colour changes; Offset printing; Artificial neural networks